Earthquake effects on youth: understanding psychological challenges and support needs - Mehmet Şam; Göcan Sever; Habibe Yildiz Yüksel; Ramin Aliyev (BMC Psychology)
Abstract The aim of this study is to examine the effects of the earthquake on the psychological symptoms of high school students, and to understand the readiness of school counseling services based on the available data. In this context, the research was designed within the scope of two different studies: Study 1: The views of school counselors, and students on the difficulties experienced due to the earthquake. Study 2: The effects of the earthquake on students’ psychological symptoms. In accordance with the purpose of the Study 1, phenomenological design, one of the qualitative research methods, was used. Findings of Study 1 signified that the students experienced academic, psychological, social, and physiological difficulties due to the earthquake. It was concluded that the students coped with the effects of the earthquake by receiving environmental support, and using optimistic thinking. School psychological counselors stated that they observed difficulties such as loss, and mourning, and absence from school in students due to the earthquake during their meetings with them. They also expressed that the students needed more academic, and psychological help after the earthquake, and they planned to deal with psychological, and academic issues in the coming period. Results of Study 2 pointed out that 246 individuals (43.3%) scored 37 or above on the Impact of Event Scale-Revised (IES-R). This indicated that these individuals had severe impact of the event/trauma symptoms. SEM analysis revealed that IES-R scores had a total effect of 0.67 on anxiety, 0.69 on depression, 0.68 on negative self-concept, 0.68 on somatisation, and 0.63 on hostility scores. In addition, the scores of the female students related to the variables such as anxiety, depression, negative self-concept, somatisation, hostility, and impact of events were significantly higher than the male students. Also, the students who lost their relatives due to the earthquake had significantly higher scores than those who did not lose their relatives in all the variables except somatisation. Besides, the students who had to change their locations after the earthquake had significantly higher scores than those who did not have to change their locations in terms of the impact of events.